Marketing of Processed Fish Products and Influencing Factors - Akhyudelpa, Yefrina; Lita, Ratni Prima; Yeni, Yulia Hendri (Jurnal Perikanan dan Kelautan, 2023)
The boundaries of the water’s Exclusive Economic Zone in West Sumatra Province are ± 186,500 km², and have the potential to produce as much as ± 340,930 tons/year in 2004. In 2007, there was a decrease in marine fish production to 187,092 tons. Three important elements of the market, namely (a) human will; (b) the desire to have; (c) the ability to shop. A group of people in pursuing the business of processing fresh fish, making semi-finished products, as well as finished products is the purpose of fish processors. The environment around the business that has a direct impact on business operations is the marketing environment. The big influence that also affects the marketing of fish to fishery business actors or micro, small and medium enterprises in the city of Padang is also caused by environmental factors used to In this study using a survey method that looks directly at each activity and conditions that exist in the research area related to problems that occur when marketing processed fish which is also an analysis of the factors that can affect fish consumption by consumers of Micro, Small and Medium Enterprises Micro, Small and Medium Enterprises.